Prevalence of overweight and obesity in 3-to-10-year-old children: assessment of different cut-off criteria WHO-IOTF - GAMA,AUGUSTA (2020)
Abstract This study compares the prevalence of overweight and obesity between WHO/IOTF criteria. A total of 17,277 Portuguese children aged 3-10 years old were analysed. The prevalences of overweight-obesity were higher at WHO classification (19.8%-20.7%) than at IOTF classification (8.2%-16.1%), (p<0.001). Agreement between the criteria were substantial for overweight (Kappa= 0.67, p<0.001) and moderate for obesity (Kappa= 0.47, p<0.001). The prevalences ratio for inequality between criteria were greater for boys than for girls and lesser for children aged 6-7 than children aged 8-10 years old. The disparities between the two criteria and the higher overweight obesity prevalences highlight the needs to develop more studies.